Designs on you - Burton, Jaci (Berkley Romance, 2024)
"Natalie Parker is in her mid-thirties, divorced, and firmly focused on her newly resurrected career and her two children. When her sister asks her to help design the backyard in the new home she shares with her boyfriend, Linc, Natalie's more than happy to take on the project. What she isn't prepared for is Linc's younger brother, video game designer Eugene Kennedy. He's smart, incredibly good-looking, and constantly flirts with Natalie. He's also too young for her, which makes him totally off-limits. Eugene is intrigued by Natalie's beauty, smarts, and especially her sarcastic wit. When he teases her, she throws it right back at him. Besides that, they have an instant chemistry, but she keeps trying to get rid of him despite the sparks that fly between them. And Eugene never backs down from a challenge. Natalie is running out of reasons to think being with Eugene is a bad thing. Her kids adore him, her sister loves him, and even her always negative mother does, too. The only person holding her back is...her. Maybe it's time she take that leap and design herself a love for the ages. After all, if she can create the perfect home, she sure as hell can design a happily ever after"--